Transcending Individual Approach of Consumption: an Investigation of Automobile Meanings by The Household Perspective - Maribel Carvalho Suarez; Leticia Moreira Casotti (BBR: Brazilian Business Review)
In consumer behavior area, families are identified as fundamental reference group in the consumption process. Historically, research involving purchasing decisions have, mostly, focused on individual decisions without regard to the dynamics of interact ions within this important group. Using a qualitative approach, based on the itinerary method this paper investigates how the meanings related to the purchase of a car help shape relationships within the family, when investigating consumption. Based on inte rviews and observations with several members of ten São Paulo families, this study highlights the cars as artifacts able to demarcate family values and hierarchies, it acts as an important "educational" and transition tool to adult life of the children.